Domain insertion permissibility-guided engineering of allostery in ion channels - Willow Coyote-Maestas (Nature Portfolio, 2019)
Allostery is a fundamental principle of protein regulation that remains challenging to engineer. Here authors screen human Inward Rectifier K + Channel Kir2.1 for permissibility to domain insertions and propose that differential permissibility is a metric of latent allosteric capacity in Kir2.1.